2022
DOI: 10.3389/fnagi.2021.769405
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and Cognition: What We Know and Where We Need to Go

Abstract: Although a causal association remains to be determined, epidemiologic evidence suggests an association between hearing loss and increased risk of dementia. If we determine the association is causal, opportunity for targeted intervention for hearing loss may play a fundamental role in dementia prevention. In this discussion, we summarize current research on the association between hearing loss and dementia and review potential casual mechanisms behind the association (e.g., sensory-deprivation hypothesis, infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 141 publications
(185 reference statements)
0
46
0
3
Order By: Relevance
“…Indeed, many prospective cohort studies have shown a positive effect of hearing aid use on cognitive function and dementia risk reduction. [47][48][49] These results may indicate that individuals with poorer cognition might be having hearing aids prescribed to them more often, but probably at a time when their cognition is so deteriorated that the aid does not exert any meaningful protective effect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, many prospective cohort studies have shown a positive effect of hearing aid use on cognitive function and dementia risk reduction. [47][48][49] These results may indicate that individuals with poorer cognition might be having hearing aids prescribed to them more often, but probably at a time when their cognition is so deteriorated that the aid does not exert any meaningful protective effect.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we found an unexpected association between an effective use of a hearing aid with poorer cognition, which may be explained by reverse causality bias resulting from our cross‐sectional design. Indeed, many prospective cohort studies have shown a positive effect of hearing aid use on cognitive function and dementia risk reduction 47–49 . These results may indicate that individuals with poorer cognition might be having hearing aids prescribed to them more often, but probably at a time when their cognition is so deteriorated that the aid does not exert any meaningful protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Those results support the idea that perhaps sensory deprivation mechanisms may play a role in the association of hearing loss and cognitive decline in the oldest-to-old. In addition to hearing loss, other factors that are associated with hearing loss such as social isolation, depression and frailty may contribute to sensory deprivation in this group,38 and future research should aim to study the influence of such additional factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have suggested a link between hearing loss-assessed both by pure tones and recently by speech discrimination-and patients' cognitive status (2,8,21,22), limited research has investigated the potential reverse relationship, where cognitive performance might itself influence audiometric testing results. Traditionally, speech discrimination is thought to require greater central processing than pure-tone audiometry and is more representative of functional hearing ability (22). Yet, the current study suggests instead that WRSs are largely driven by pure-tone thresholds requiring limited central processing, which results in minimal explanatory influence attributable to cognitive performance status.…”
Section: Discussionmentioning
confidence: 99%